TEORI YANG MELANDASI PEMBELAJARAN KONSTRUKTIVISTIK - Haryanto Haryanto (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The discussion and study for constructivist-learning approach is usually interms of the how the theory is implemented. The study is usually pe1formedby comparing the differences between the constructivist approaches ll'ithother approaches, i.e.: behaviorist. The whys is still too far to answer. It isfor this reason, author is trying to describe some theory that is the basis olconstructivist theory to enrich references in constructivist learning. Somefundamental theories of constructivist learning are Piaget theOJJ' 011scheme, assimilation, accommodation and equilibration, Vygotsky theo1J'on Zone of Proximal Development (ZPD), Bruners theory on discove1J'learning, Ausubel theory on meaningful learning and semiotic interactions.